The Sensitivity of Sag 1 and Bag 1 Probes to Detect Toxoplasma gondii in The Free-Rearing Chicken - Ida Ayu Pasti Apsari (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
This study was aimed to determine the sensitivity of Sag1 and Bag1 Probe to detect in free-rearing chicken using dot blot hybridization method. Thirty serologically free-rearing chicken toxoplasmosis DNA were used as samples in this study. Sag1 and Bag1 probes were labeled by non-radioactive Dig-11-dUTP. The success of detection was based on the establishment of colored dot on the nylon membrane after detected with antibody-antiDig. The Sensitivity test of Sag1 and Bag1 probes in detection were conducted by making serial dilutions of the dot blot hybridization positive free-rearing chicken DNA. The results showed that 19 positive samples detected by Sag1 and Bag1 probe by dot blot hybridization method. The sensitivity of 5.87 pg / μl Bag1 probe to detect free-range chicken DNA was 0.23 ng / μl , and sensitivity of 6.72 pg / μl Sag1 Probe was 0.45 ng / μl. From the resuls above it can be concluded that the Bag1 probe was more sensitive than that of the Sag1 probe to detect Toxoplasma gondii of free-range chicken DNA.Keywords : Toxoplasma gondii; Sag1 and Bag1 Probe; Dig-11-dUTP; free-rearing chicken